2002
DOI: 10.1002/ijc.10673
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mammographic densities and their determinants in women from Japan and Hawaii

Abstract: Breast cancer incidence increases considerably in women who migrate from Japan to the United States. Based on the hypothesis that mammographic density in healthy mammograms reflects differences in breast cancer risk, we compared mammographic density in 3 groups of women at different levels of risk: Caucasian and Japanese women in Hawaii and Japanese women in Japan. In a cross-sectional design, preand postmenopausal women without a history of breast cancer and with a mammogram free of suspicious lesions were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
39
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 29 publications
10
39
3
Order By: Relevance
“…The results relating reproductive events (nulliparity, age at first birth, number of children) to breast density are in accordance with data previously reported [23][24][25]. Those studies demonstrate consistent patterns of association between these well-recognised breast cancer risk factors [6] and breast density, irrespective of the manner in which density is assessed (BI-RADS, Tabar, percent area density) across ethnically diverse populations.…”
Section: Main Findings and Interpretationsupporting
confidence: 90%
See 1 more Smart Citation
“…The results relating reproductive events (nulliparity, age at first birth, number of children) to breast density are in accordance with data previously reported [23][24][25]. Those studies demonstrate consistent patterns of association between these well-recognised breast cancer risk factors [6] and breast density, irrespective of the manner in which density is assessed (BI-RADS, Tabar, percent area density) across ethnically diverse populations.…”
Section: Main Findings and Interpretationsupporting
confidence: 90%
“…Previous studies have found the opposite [23,31] or no association [24,25], as in the current study. The close proximity to reporting and occurrence of menarche in our study gives greater weight to our finding as its timing is likely to have been accurately recalled over the short period since its occurrence.…”
Section: Main Findings and Interpretationsupporting
confidence: 59%
“…Previous studies have found positive relationships between age at menarche and breast density (El-Bastawissi et al, 2000;Sala et al, 2000), although in this and other previous studies (Jakes et al, 2000;Maskarinec et al, 2002;Heng et al, 2004) such associations have not been demonstrated. Lower parity and later age at first pregnancy are two of the most consistently reported risk factors for breast cancer (Kelsey et al, 1993), and have also been shown to be related to breast density in later life (Heine and Malhotra, 2002), most recently using both SCC and SMF methods in a sample of 250 women in England (McCormack et al, 2007).…”
Section: Discussioncontrasting
confidence: 65%
“…Because the amounts of epithelial and stromal tissue as represented by the dense areas probably determine breast cancer risk (3), the size of the dense areas may provide more relevant information than percent density which is strongly influenced by body weight (38,(42)(43)(44). Nonetheless, as Fig.…”
Section: Discussionmentioning
confidence: 99%